The Effect of Good Corporate Governance on Production Effectiveness - Nita Kanya (Almana : Jurnal Manajemen dan Bisnis, 2021)
PT. PLASTIKATAMA is an industrial technology company that runs its business in the production of air pollution control equipment, anti-corrosion equipment, electro-coating systems, chemical tanks, and industrial technology goods made from fiberglass, plastic, and metal as basic materials. Constraints that are being experienced by PT. PLASTIKATAMA, namely the production process is still ineffective, this can be seen from the lack of achievement of targets such as there are still obstacles in the timeliness of producing products, the inaccurate quality of the products produced. The purpose of the author in conducting research is: to know the implementation of Good Corporate Governance at PT. PLASTIKATAMA, to determine the effectiveness of production at PT. PLASTIKATAMA, knowing the influence of Good Corporate Governance on the production process on the effectiveness of the production of PT. PLASTIKATAMA. The results of this study can be used as input and information about the implementation of Good Corporate Governance so that it can be used as a basis for determining the effectiveness of the company's production. For employees at PT. PLASTIKATAMA provides information about the effectiveness of company production and Good Corporate Governance.